2020
DOI: 10.18280/eesrj.070404
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ground Magnetic Geophysical Method in the Delineation of Subsurface Structures of Dala Hill in Kano Ancient City, Northwest Nigeria

Abstract: Ground Magnetic measurement was carried out with the aim of delineating the subsurface structures on Dala hill, Kano State. Total magnetic intensity data were acquired using the SCINTREX proton precession magnetometer along closely spaced traverses. The acquired total magnetic intensity data were reduced and plotted using Golden Surfer software to produce the 2D and 3D surface maps for visual inspection. Five profiles AB, CD, EF, GH and IJ were selected for forward modelling using Mag2dc software to give detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…Considering Profile 1, which was taken from the northwestern part of the study area, an intrusion can be observed at the top layer and extends into the weathered layer, covering a total depth range of 2-48 m. This intrusion is characterized by a high resistivity of iron ore, and seems to contain possible iron ore as it shows a good correlation with low chargeability inversion. Additionally, the presence of this intrusion aligns with findings from the ground magnetic survey conducted by Shehu et al [8], further supporting the potential for iron ore mineralization in this area.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Considering Profile 1, which was taken from the northwestern part of the study area, an intrusion can be observed at the top layer and extends into the weathered layer, covering a total depth range of 2-48 m. This intrusion is characterized by a high resistivity of iron ore, and seems to contain possible iron ore as it shows a good correlation with low chargeability inversion. Additionally, the presence of this intrusion aligns with findings from the ground magnetic survey conducted by Shehu et al [8], further supporting the potential for iron ore mineralization in this area.…”
Section: Discussionsupporting
confidence: 85%
“…Shehu et al [8] conducted a ground magnetic study to delineate the subsurface structures of Dala Hill. Two classes of anomalies were discovered, with the shallow anomalies correlated with the anthropogenic activities of https://doi.org/10.56578/atg030104 ancient settlers and the deep ones associated with internal geologic features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic method was also used as a means in ground water investigation in a basement complex terrain with a view to delineate the subsurface structure, estimate the overburden thickness and access groundwater in the locality (Oni et al, 2020). Ground magnetic measurement was as well carried out with the aim of delineating the subsurface structures on Dala hill, Kano State in the studies carried out by (Shehu et al, 2020). A Ground magnetic survey was equally done to investigate the presence of an iron ore deposit at Oke Aro in Iseyin East, Southwest Nigeria (Adebisi, 2018).…”
Section: Introductionmentioning
confidence: 99%